2016
DOI: 10.1080/09540121.2016.1259451
|View full text |Cite
|
Sign up to set email alerts
|

“It is easier for me to shoot up”: stigma, abandonment, and why HIV-positive drug users in Russia fail to link to HIV care

Abstract: Many HIV-positive people who inject drugs (PWID) globally are not receiving HIV care. This represents a major challenge among key populations to end the global HIV epidemic. This qualitative study explored the process and associated barriers of linking HIV-positive PWID who are in addiction treatment to HIV care in St. Petersburg, Russia. We conducted three focus groups and seven semi-structured interviews with participants in the LINC (“Linking Infectious and Narcology Care”) project at addiction and HIV hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 28 publications
0
36
0
1
Order By: Relevance
“…Stigma and negative attitudes toward PLWH by health care providers can manifest in poor patient-provider relationships and denial of proper care (8, 1015), and continue to be a focus of stigma interventions (1622). Stigma and discrimination are also directed toward providers who treat HIV patients (23) and can perpetuate an unwillingness to treat PLWH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stigma and negative attitudes toward PLWH by health care providers can manifest in poor patient-provider relationships and denial of proper care (8, 1015), and continue to be a focus of stigma interventions (1622). Stigma and discrimination are also directed toward providers who treat HIV patients (23) and can perpetuate an unwillingness to treat PLWH.…”
Section: Introductionmentioning
confidence: 99%
“…Stigma and discrimination has also been found associated with a decreased willingness to disclose one’s HIV status, which in turn may lead to depression and anxiety (2, 2427). Stigma and discrimination in health care settings lead to PLWH hiding their HIV status from providers (8, 27, 28), creating a primary barrier to HIV testing (7, 12, 29, 30) and care-seeking (7, 10, 31). A meta-analysis of global studies published between 1996 and 2013 found that people who had experienced HIV-related stigma were at greater risk of depression, lower social support, and “were 21% less likely to access or use health and social services” (32).…”
Section: Introductionmentioning
confidence: 99%
“…Three qualitative studies from Ukraine ( n = 16), India ( n = 19) and Russia ( n = 42) revealed that health professionals held assumptions in relation to HIV‐positive drug users’ poor adherence and refused to treat them . Aside from health professionals’ negative assumptions of drug users, Pach et al .…”
Section: Resultsmentioning
confidence: 99%
“…'s ( n = 34) and Kiriazova et al . 's qualitative studies ( n = 25) indicated that some drug users did not trust health professionals either. This created the barrier to accessing HIV care.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation